INFLUENCE OF HAES-LX-5% INFUSION SOLUTION ON THE DNA CONTENT OF ENDOCRINE GLANDS CELLS AGAINST THE BACKGROUND OF THERMAL BURN OF SKIN IN RATS - Cherkasov, V.G.; Dzevulska І.V.; Cherkasov, E.V.; Kaminsky, R.F.; Pastukhova, V.A.; Kovalchuk О.І.; Trofimenko, Yu.Yu. (World of Medicine and Biology, 2017)
The results of the experimental study of the DNA content by the method of duct DNA cytometry in adenohypophysis, thymus and adrenal glands cells on the background of thermal burn of the skin and correction of the HAES-LX-5% infusion solution in comparison with a similar burn on the background of application of 0.9% solution are given in the article. NaCl. The use of the HAES-LX-5% drug causes a positive polyfactorial effect on the DNA content in adenohypophysis, thymus and adrenal cells. Its effect has specific manifestations in each of the cell groups and provides a balance recovery between the processes of DNA synthesis and apoptosis. So the use of this infusion solution softens the negative impact of the adverse effects of skin burn in adenohypophysis cells, mainly affecting synthetic processes, which is especially manifested in the delay in the development of burn disease. In adrenal cells, the HAES-LX-5% solution more definitely reduces the symptoms of apoptosis from day 7 of the experiment, rather than affecting synthetic processes. The effect of this solution on the content of thymus DNA cells consists in the reducing the parameters of the interval SUB-G0G1 practically in all terms of the experimental study with simultaneous insignificant increase of synthetic processes.